Pendidik, Fungsi dan Tugasnya - Sitika, Achmad Junaedi; Rahmadian, Alia; Nindya, Nindya; Rahmadina, Firda; Novariyanti, Vani; Gustian, Rafi Dwi; Karhali, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the educational process, the role of educators is very important in achieving educational goals. Educators, whether as parents or professionals, are responsible for the development of students. Parents are the first and primary educators, while the second educator is the teacher, mentor, or caregiver. Educators are responsible for the implementation of education with a focus on students. Students experience education in three environments: family, school, and society. Therefore, parents are responsible for education in the family, teachers in the school, and people involved in educational activities in the community. Education takes place in social interaction, where every interaction between adults and children is a place of education. And in Islamic education, the concept of education is based on the teachings of the Quran and the hadiths of Prophet Muhammad SAW. Allah SWT is the main educator, who through His revelation, bestows guidance and mercy upon humanity.